A Comprehensive Description of Postpartum Pain after Cesarean Delivery. Issue 6 (14th August 2014) - Chin, Emily G.; Vincent, Catherine; Wilkie, Diana
ABSTRACT Objective To describe women's experiences with the perception of, evaluation of, and response to postpartum pain after cesarean delivery through the sensory, affective, cognitive, and behavioral dimensions of pain. The secondary aim of this research was to differentiate pain described with nociceptive and neuropathic pain descriptors. Design Longitudinal, concurrent mixed methods design. Setting Large, university‐based, midwestern medical center. Participants Convenience sample of 30 low‐risk women scheduled for cesarean deliveries. Methods The PAINReportIt, a computerized version of the McGill Pain Questionnaire, was administered in person to participants at two visits: between 24 and 48 hours postcesarean delivery and at 6 weeks postpartum. Descriptive statistics, t tests, and χ2 tests were calculated from these data and pain descriptor selections were compared with established nociceptive and neuropathic pain descriptor lists. Results Pain was reported in all dimensions at both visits. The abdomen was most frequently selected for pain location; mean intensity was 2.75/10 at the first visit, 1.1/10 at the 6‐week visit. Pain in the sensory and cognitive dimensions decreased significantly between visits. Affective dimension pain decreased, but the difference was not significant. Participants reported activities that increased and decreased pain in the behavioral dimension. Pain descriptors indicative of nociceptive (e.g., tender, sore) and neuropathic (e.g. aching) pain were selected at both visits. Conclusion Postpartum pain after cesarean delivery is multidimensional and has been described with words indicative of nociceptive and neuropathic pain. Nurses should complete a thorough and comprehensive pain assessment throughout the postpartum for patients experiencing cesarean deliveries.